Culture, children and couple gender inequality - Jonas Jessen (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This paper examines how culture impacts within-couple gender inequality. Exploiting the setting of Germany's division and reunification, I compare child penalties of couples socialised in a more gender-egalitarian culture (East Germany) to those in a gender-traditional culture (West Germany). Using a household panel, I show that the long-run child penalty on the female income share is 26.9 percentage points in West German couples, compared to 15.5 in East German couples. I additionally show that among women in West Germany the arrival of a child leads to a greater increase in housework and a larger share of child care responsibilities than among women in the East. A battery of robustness checks confirms that differences between East and West socialised couples are not driven by current location, economic factors, day care availability or other smooth regional gradients. I add to the main findings by using time-use diary data from the German Democratic Republic (GDR) and reunified Germany, comparing parents with childless couples of similar age. This provides a rare insight into gender inequality in the GDR and allows to compare the effect of children in the GDR to the effects in East and West Germany after reunification. Lastly, I show that attitudes towards maternal employment are more egalitarian among East Germans, but that the arrival of children leads to more traditional attitudes for both East and West Germans. The findings confirm that socialisation has a strong impact on child penalties and thus on gender inequality as a whole.
Keywords: J16; J22; D1; 330; cultural norms; gender inequality; child penalty